The Efficacy of Misoprostol and Prostaglandin E2 in Induction of Labor - Burhan, Samreen; Anwar, Samdana (Indus Journal of Bioscience Research, 2025)
Background: In fact, induction of labor (delivery) is commonly performed as an obstetric intervention when the risks of continuing the pregnancy outweigh the benefits. For cervical ripening and labor induction, the pharmacological agents most used are misoprostol (prostaglandin E1 analogue) and dinoprostone (prostaglandin E2). The objective of this study was to compare the efficacy of misoprostol versus prostaglandin E2 in induction of labour in term pregnant women at a tertiary care hospital. Methods: It was an interventional randomized controlled trial lasting three months duration at Mercy Teaching Hospital and Kuwait Hospital, Peshawar from 25 Feb 2025 to 25 March 2025. Random assignment of 230 women who fulfilled the inclusion criteria was undertaken to receive misoprostol (25 µg vaginally every 6 hours, max 4 doses) or Prostaglandin E2 (2 mg vaginally every 12 hours, max 2 doses). Onset of labour with no further intervention was defined as successful induction. SPSS version 25 was used to analyze the data and the p-value < 0.05 was considered significant. Results: The success rate of induction was 97.4% with misoprostol compared with 90.4% with prostaglandin E2 (p = 0.031). Among the significant variables included in subgroups analysis by age, parity, BMI, gestational age and residence, misoprostol consistently demonstrated higher efficacy. Conclusion: Prostaglandin E2 was less effective in inducing labor than was misoprostol. Because of its low cost, ease of storage and high success rate, this reduces the use of its broader use, especially in low resource settings. We recommend further studies evaluating safety outcomes and long term maternal and neonatal implication.